ANALISIS HISTOLOGI INSANG KUDA LAUT YANG DIAMBIL DARI PENANGKARAN PULAU BADI - Indra Ahmad (LPPM Institut Pendidikan Nusantara Global, 2023)
Sea Horse (Hippocampus barbouri) breeding is not immune to disease. The gills are the first organ exposed to disease. This study aims to look at the histopathological shape of healthy and diseased gills so that differences can be seen. Seahorse gill samples were fixed with 70% PA alcohol and then histology preparations were made by staining with hematoxylin and eosin (HE). The data obtained were analyzed descriptively. The results of this study found the presence of inflammatory infiltration in healthy gills and hyperplasia in diseased gills.